Thermal treatment at induction heating and structure of steel grit, hardened from melt - P. S. Gurchenko; M. I. Demin; A. I. Komarov (Литьë и металлургия)
There is shown that the created on MAZ technology and equipment of thermal processing of grit at induction heating allows to regulate the temperature of processing and to provide the solidity of grid in the specified interval taking into account the changing of the chemical composition.